Identifikasi Pengaruh Lokasi Kegiatan Industri Migas Terhadap Harga Lahan di Kabupaten Bojonegoro - Hanafi Kholifatul Iman; Adenantera Dwicaksono (Politeknik Statistika STIS, 2022)
The dynamics of land use change implies changes that occur and the use of resources in an area. Gayam District, because of the division, has succeeded in becoming a sub-district with a high level of economic change with the presence of an operating oil and gas drilling area. The purpose of this study was to identify the contribution of the oil and gas industry to changes in land prices in Gayam District. Methods of data collection is done by observation, interviews, and secondary data. This study uses quantitative methods with descriptive statistical analysis, spatial, and spatial statistical modeling to obtain a model of the impact of industrial activities on land prices. This study results that the Spatial Lag Regression Model can explain the model up to 89.21%. It is concluded that the Spatial Lag Model provides the best value in explaining the land price model in Gayam District. However, there are still indications of bias variables in non-built areas, number of facilities, and pollution. Therefore, it can be concluded from this modeling that there is no convincing evidence that oil and gas drilling activities have an impact on land prices.